X-ray fluorescence melting sample preparation method of aluminum nitride - BAI WANLI (2021)
The invention provides an X-ray fluorescence melting sample preparation method of aluminum nitride, and belongs to the technical field of aluminum nitride impurity component analysis and detection. The method comprises the following steps: adding an acid liquor into aluminum nitride for acidolysis to obtain acidolysis gel; burning the acidolysis gel to obtain aluminum oxide; and adding a melting reagent and a release agent into the aluminum oxide, melting, and pouring a sample sheet to obtain a sample sheet. According to the method, the transparent, smooth and uniform sample sheet can be prepared, the problem that forming is difficult in conventional aluminum nitride melting sample preparation is solved, and a new method for aluminum nitride melting sample preparation is developed. 本发明提供了一种氮化铝的X射线荧光熔融制样方法，属于氮化铝杂质成分分析检测技术领域，所述方法包括：向氮化铝中加入酸液进行酸解，获得酸解凝胶体；将所述酸解凝胶体进行灼烧，获得氧化铝；向所述氧化铝中加入熔融试剂和脱模剂，熔融后进行样片浇注，获得样片。该方法能够制得透明、光滑、均匀的样片，解决了常规氮化铝熔融制样难以成型的问题，开发了氮化铝熔融制样的新方法。